Pelatihan Akuntansi Digital pada Siswa SMA di Semarang - Anton Anton; Cristeddy Asa Bakti; Zewindra Zai; Aghistia Fikka Finata; Damar Putri Ayu Ningsih Bate’e; Aprilya Aisyah (Jurnal Pengabdian Bisnis dan Akuntansi, 2025)
The rapid advancement of information technology today has brought significant changes toward the era of digitalization, with many business activities now being conducted digitally. One such development is the transformation of accounting systems into digital formats, encompassing the identification, classification, and summarization of transactions through the use of digital technology. SMA Kristen YSKI Semarang, a private high school located in Semarang, has yet to implement technology-based learning that supports business activities. As a result, students are not familiar with commonly used digital applications in the business world. One widely used application in the business sector is the digital accounting application, Spreadsheet. Therefore, this Community Service activity aimed to provide training for students to introduce and teach the use of digital accounting applications for recording business activities and to enhance the skills of SMA Kristen YSKI Semarang students, enabling them to be more competitive in the job market after graduation. The training was conducted through hands-on application of Spreadsheet usage based on given case studies. Based on the students’ responses to the questionnaire, it was evident that there was an increase in their understanding of digital accounting (Spreadsheet application) before and after the training.